2016
DOI: 10.1104/pp.15.01921
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of rice WRKY62 and WRKY76 transcription factor genes in pathogen defense

Abstract: The WRKY family of transcription factors (TFs) functions as transcriptional activators or repressors in various signaling pathways. In this study, we discovered that OsWRKY62 and OsWRKY76, two genes of the WRKY IIa subfamily, undergo constitutive and inducible alternative splicing. The full-length OsWRKY62.1 and OsWRKY76.1 proteins formed homocomplexes and heterocomplexes, and the heterocomplex dominates in the nuclei when analyzed in Nicotiana benthamiana leaves. Transgenic overexpression of OsWRKY62.1 and Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
145
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 49 publications
5
145
0
Order By: Relevance
“…Based on the results of our previous work, we presumed that SA induced some OsTGA or OsWRKY proteins to repress JA/ET‐dependent RSOsPR10 expression (Takeuchi et al., ). In fact, WRKY factors are known to function not only as positive regulators but also as negative regulators by targeting a number of defense‐related genes and regulating their expression through binding to W box(es) in their promoters (Birkenbihl, Kracher, & Somssich, ; Liu, Chen, et al., ). As shown in Figures and , the 3‐kb promoter region closely mimicked the in vivo expression pattern of RSOsPR10, that is, JA/ET induction, SA suppression, and root‐specific expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the results of our previous work, we presumed that SA induced some OsTGA or OsWRKY proteins to repress JA/ET‐dependent RSOsPR10 expression (Takeuchi et al., ). In fact, WRKY factors are known to function not only as positive regulators but also as negative regulators by targeting a number of defense‐related genes and regulating their expression through binding to W box(es) in their promoters (Birkenbihl, Kracher, & Somssich, ; Liu, Chen, et al., ). As shown in Figures and , the 3‐kb promoter region closely mimicked the in vivo expression pattern of RSOsPR10, that is, JA/ET induction, SA suppression, and root‐specific expression.…”
Section: Resultsmentioning
confidence: 99%
“…More recent results of a study on alternative splicing variants of OsWRKY62 and OsWRKY76 transcripts indicated that short variant of OsWRKY76.2 with the LxLxLx motif at the N‐terminus exhibited repressor activity, but OsWRKY62 lacking the LxLxLx motif at the N‐terminal also had repressor activity, which was attributed to two short sequences, PTDDS and EDLEEK (Fig. ) (Liu, Chen, et al., ). Further research is required to identify the amino acid sequence motif(s) responsible for the repressor activity of these OsWRKYs and to determine which protein is the corepressor.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…oryzae. [10] Similarly, transgenic lines with the GhWRKY27a gene exhibited more severe disease symptoms after Rhizoctonia solani infection in Nicotiana benthamiana. [11] By contrast, mutations of AtWRKY70 reduced the plant tolerance to the bacterial pathogen Erwinia carotovora as well as to the fungal pathogens Erysiphe cichoracearum and Botrytis.…”
Section: Introductionmentioning
confidence: 99%